227k views
1 vote
I need help with number 12 and can you please write your final answer using only positive exponents

I need help with number 12 and can you please write your final answer using only positive-example-1

1 Answer

3 votes

Solution:

Given the expression:


(y^9\cdot y^8)/(y^4)

The above expression can be further expressed as


(y^9* y^8)/(y^4)

From the laws of exponents,


\begin{gathered} a^x* a^y=a^((x+y)) \\ (a^x)/(a^y)=a^((x-y)) \end{gathered}

Thus, we have


\begin{gathered} (y^9* y^8)/(y^4)=(y^((9+8)))/(y^4) \\ =(y^(17))/(y^4) \\ recall\text{ that} \\ (a^x)/(a^y)=a^((x-y)) \\ thus,\text{ we have} \\ (y^(17))/(y^(4))=y^((17-4)) \\ \Rightarrow y^(13) \end{gathered}

Hence, we have


y^(13)

User Yukulelix
by
4.6k points